The Relationship between Job Training and Employee Performance Mediated by Work Competence in Manufacturing Companies in Semarang City - Safira Arbella Aurell Urrofik; Tri Suminar; Habibie BTE HJ Ibrahim (Universitas Negeri Semarang, 2023)
Technology is developing more rapidly, so competencies are needed following the demands of today's times so that human resources can produce more effective performance by utilizing technological advances. The purpose of this study is to analyses the relationship between job training and employee work competence, the relationship between work competence and employee performance in the company, the direct relationship between job training and employee performance, and analyses the indirect relationship between job training and employee performance through work competence in employees of manufacturing companies in Semarang City. The research was conducted using a quantitative approach with an ex-post facto method. The study population is employees of manufacturing companies in Semarang City who attended job training according to their field of expertise in the last year. The results showed that job training has a significant relationship with work competence. (2) Work competence has a significant relationship with employee performance. (3) Job training has a significant direct relationship with employee performance. (4) Job training does not have a significant relationship with employee performance through work competencies. The research concluded that job training with work competence through work competence is positive but insignificant. In contrast, the relationship between job training with employee performance is directly significant. This research provides benefits, especially for organizations or companies, in making decisions related to human resource development through training programs to improve employee work competence and performance.